MANAJEMEN KEUANGAN KELUARGA GUNA MENUJU KELUARGA SEJAHTERA - Rodhiyah, Rodhiyah (FORUM)
Abstract: Money is any object that is generally accepted as payment for goods and services that is important for a moderncivilization. It also has function as instrument for accumulating wealth as well as asset in order to guarantee prosperity. In order to achieve good financial suppot a family should do a financial management, which provides financial strategy: planning; utilizing; evaluating in order to maintain effective and efficient family consumption. This article discusses the description of financial management; how to do it and who should do it.Keyword : Prosperity, Family, Financial Managementpermalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3202